2020
DOI: 10.1172/jci139741
|View full text |Cite
|
Sign up to set email alerts
|

Truncated stathmin-2 is a marker of TDP-43 pathology in frontotemporal dementia

Abstract: No treatment for frontotemporal dementia (FTD), the second most common early-onset dementia, is available but therapeutics are being investigated to target the two main proteins associated with FTD pathological subtypes: TDP-43 (FTLD-TDP) and tau (FTLD-tau). Testing potential therapies in clinical trials is hamstrung by our inability to distinguish between patients with FTLD-TDP and FTLD-tau. Therefore, we evaluated truncated stathmin-2 (STMN2) as a proxy of TDP-43 pathology, given reports that TDP-43 dysfunct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
207
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(219 citation statements)
references
References 67 publications
12
207
0
Order By: Relevance
“…As such, the STMN2 multiallelic CA repeat is more informative than previously reported biallelic single nucleotide polymorphisms ( Landers et al, 2009 ; Blasco et al, 2011 ; Diekstra et al, 2012 ; ALSGEN, 2013 ; Lopez-Lopez et al, 2014 ; Fogh et al, 2016 ; Theunissen et al, 2020 ), and may explain disease risk in a larger population of sALS patients. As a critical neuronal maintenance factor ( Shin et al, 2014 ; Klim et al, 2019 ), attenuating STMN2 expression may be a viable therapeutic approach to modify disease in a large proportion of both fALS and sALS patients, and reinforces its potential development for use as a prognostic marker or in clinical trials for ALS ( Klim et al, 2019 ; Melamed et al, 2019 ) and other neurodegenerative diseases ( Wang et al, 2019 ; Prudencio et al, 2020 ).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…As such, the STMN2 multiallelic CA repeat is more informative than previously reported biallelic single nucleotide polymorphisms ( Landers et al, 2009 ; Blasco et al, 2011 ; Diekstra et al, 2012 ; ALSGEN, 2013 ; Lopez-Lopez et al, 2014 ; Fogh et al, 2016 ; Theunissen et al, 2020 ), and may explain disease risk in a larger population of sALS patients. As a critical neuronal maintenance factor ( Shin et al, 2014 ; Klim et al, 2019 ), attenuating STMN2 expression may be a viable therapeutic approach to modify disease in a large proportion of both fALS and sALS patients, and reinforces its potential development for use as a prognostic marker or in clinical trials for ALS ( Klim et al, 2019 ; Melamed et al, 2019 ) and other neurodegenerative diseases ( Wang et al, 2019 ; Prudencio et al, 2020 ).…”
Section: Discussionmentioning
confidence: 85%
“…Reduced STMN2 expression has been reported not only in iPSC derived motor neurons in sALS and familial ALS cases with TDP-43 pathology, but also in motor cortex and spinal motor neurons of fALS and sALS patients with C9orf72 repeat expansions, the most common inherited form of ALS ( Melamed et al, 2019 ). Additionally, reduced STMN2 expression has more recently been reported in the brain of patients with Parkinson’s disease ( Wang et al, 2019 ), and frontotemporal dementia ( Prudencio et al, 2020 ). Further supporting the finding we present here, it was also reported that levels of full length STMN2 were not always correlated to phosphorylated TDP-43 burden in patients with frontotemporal dementia ( Prudencio et al, 2020 ), suggesting that other factors outside the TDP-43/cryptic exon mechanism may contribute to regulation of STMN2 expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Melamed et al proposed that ALS is associated with loss of nuclear TDP-43 [117]. Their results confirm that reduction of nuclear TDP-43 inhibits regeneration of motor axons, which is the consequence of reduction in stathmin-2 (STMN2), an essential protein for axonal growth and maintenance ( Figure 3B) [117,118].…”
Section: Tardbpmentioning
confidence: 78%
“…Specifically, we detected downregulation of neuronal growth associated protein stathmin-2 (STMN2) and TAR DNA-binding protein 43 (TDP43/ TARDBP ) and upregulation of the non-coding RNA BC200/ BCYRN1 , which was shown to be dysregulated in AD patients’ brains (24). Expression changes of these genes are associated with AD pathogenesis (2426).…”
Section: Introductionmentioning
confidence: 99%